Analysis of the survival rate of dental implants installed in patients with osteoporosis. Systematic review with meta-analysis. - Reiner, Fabio Alexandre; Melo, Antônio Renato (Brazilian Journal of Implantology and Health Sciences, 2020)
The objective of this project was to carry out a systematic review with meta-analysis, adopting the Cochrane model for systematic reviews and meta-analyzes, in order to analyze the index of implant failures and peri- implant bone loss. The PubMed / Medline, Cochrane Collaboration, SciELO and Web of Science databases were consulted in order to select studies in the area from specific descriptors: `` osteoporosis`` and `` Dental implants``.The data were tabulated and analyzed qualitatively and quantitatively using the ReviewerManager5.3 software (Review Manager - RevMan. Version 5.3 Copenhagen; The Nordic Cochrane Center, The Cochrane Collaboration, 2014). For all the analyzed data, the statistically significant value of p <0.05 was considered. The organized and tabulated data showed that there was no significant difference in the survival rate of dental implants installed in patients with osteoporosis (p≥0.05) when compared to patients without osteoporosis, differently in terms of peri-implant bone loss, which revealed a difference greater loss of peri-implant bone tissue for patients with osteoporosis (p <0.01), however controlled and randomized clinical studies should be performed with a longer follow-up period.